Aging and Haptic-Visual Solid Shape Matching. (August 2017) - Norman, J. Farley; Adkins, Olivia C.; Dowell, Catherine J.; Hoyng, Stevie C.; Gilliam, Ashley N.; Pedersen, Lauren E.
A total of 36 younger (mean age = 21.3 years) and older adults (mean age = 73.8 years) haptically explored plastic copies of naturally shaped objects (bell peppers, Capsicum annuum ) one at a time for 7 s each. The participants' task was to then choose which of 12 concurrently visible objects had the same solid shape as the one they felt. The younger and older participants explored the object shapes using either one, three, or five fingers (there were six participants for each combination of number of fingers and age group). The outcome was different from that of previous research conducted with manmade objects. UnlikeJansson and Monaci (2006), we found that for most objects, our participants' performance was unaffected by variations in the number of fingers used for haptic exploration. While there was no significant overall effect of the number of fingers, there was a significant main effect of age. The younger adults' shape matching performance was 48.6% higher than that of the older adults. When perceiving naturally shaped objects such as bell peppers, it appears that the usage of a single finger can be as effective as haptic exploration with a whole complement of five fingers.